(untitled) (Annals of Medical Research, 2021)
Aim: In this study, we aimed to investigate the feasibility of ex vivosentinel lymph node (SLN) mapping and to evaluate efficacy of this technique on staging in patients with colorectal cancer.Material and Methods: : This single-center, prospective study included a total of 35 patients (25 males, 10 females; mean age: 55 years; range, 35 to 85 years) who were diagnosed with Stage 2 colorectal cancer between May 2015 and August 2017. All patients underwent curative surgery and SLN dissection.Results: Tumor was located in rectum in 17, in sigmoid colon in six, in right colon in seven, and in left colon in five patients. Total abdominal colectomy was performed in six, left hemicolectomy in three, right hemicolectomy in six, low anterior resection in 14, anterior resection in two, and abdominoperineal resection in four patients. Of 17 patients with clinical Stage 2 rectal cancer, 15 underwent neoadjuvant chemoradiotherapy (CRT). All patients were histopathologically diagnosed with an adenocarcinoma. Median total number of SLNs dissected was 13 with 16.9 per patient. In two patients receiving neoadjuvant CRT due to rectal cancer, a pathological complete response was achieved. The failure rate of SLNs detection was statistically significantly higher for rectal tumors than the other tumors (p=0.041) and in the patients in whom ≤7 lymph nodes dissected (p=0.023). Conclusion: Our study results suggest that SLN mapping is a useful technique with high success ratesas well as further immunohistochemical examination of the SLNs doesn’t cause stage migration. However, the success rate is lower in rectal tumors than the other tumors and in the patients with ≤7 lymph nodes dissected.